0187 Brain Connectivity and Parenting: Association between Familial Factors and Sleep EEG Coherence in Infancy. (25th May 2022) - Markovic, Andjela; Schoch, Sarah; Huber, Reto; Kohler, Malcolm; Kurth, Salome
Abstract: Introduction: Brain connectivity is tied to cognitive development and behavior. Previous work suggests that interactions with the environment tune the maturing patterns of brain connectivity. As the relevant environmental factors remain largely unknown, we examined whether the sleep-related familial context is associated with infant brain functional connectivity measured through sleep EEG coherence. Methods: At-home 124-channel sleep EEG was recorded in 31 healthy infants aged 5.5 to 7.4 months (mean age=5.9±0.5mo; 15 females). Coherence was calculated for the first 80 20-second epochs of NREM sleep in delta (0.75–4.25Hz) and sigma (9.75–14.75Hz) bands, frequencies undergoing pronounced maturational dynamics. We averaged coherence within three regions over the frontal lobe (left, central, right) identified as regions with the strongest connectivity through data-driven clustering. For these regions and bands, linear regression models quantified the association between coherence and familial context, i.e., scores from the Brief Infant Sleep Questionnaire (i.e., sleeping arrangement and bedtime routine), Baby Care Questionnaire (i.e., Structure and Attunement subscales reflecting parental principles regarding infant sleep regularity), Maternal Cognitions about Infant's Sleep (i.e., total score), age and sex. The best-fitting model was selected through backward selection (Akaike information criterion). Results: Surprisingly, sex was the most consistent contributor across regions and bands, with girls exhibiting greater coherence than boys (FDR-corrected 0.004≤p≤0.038). Furthermore, older infants showed lower sigma coherence over the right frontal lobe (FDR-corrected 0.002≤p≤0.004). Additionally, infants co-sleeping with parents or siblings demonstrated lower delta and sigma coherence over the right frontal lobe than infants sleeping in their own bed (FDR-corrected 0.001<p≤0.025). Similarly, fewer maternal worries regarding the infant's sleep were associated with lower sigma coherence in the right frontal region (FDR-corrected p=0.014). Finally, more regular bedtime routines were linked to increased delta coherence over the left frontal lobe (FDR-corrected p=0.014). Conclusion: Based on previous observations indicating that in healthy children the right hemisphere develops first with a subsequent shift in asymmetry to the left, we propose that environmental factors such as co-sleeping, fewer parental worries, and more structured sleeping routines in infancy may serve as targets for early interventions to support this process and thereby healthy brain development. Support (If Any): This work was supported by the Swiss National Science Foundation (PCEFP1 181279) and the University of Zurich (Medical Faculty; Forschungskredit FK 18 047; Stiftung für wissenschaftliche Forschung STWF 17 008).